Regulating Contracts - Collins, H (2002)
Using an interdisciplinary approach involving economics, sociology and law, Regulating Contracts explores fundamental questions about the purposes and effects of legal regulation of contractual relationships. What kind of social relation do contracts create, or, more precisely, how do contracts govern social interaction. How are contractual relations, or more generally, markets constructed? Does the law play a significant role in particular practices, and in particular, what do lawyers, courts, and legal sanctions contribute to the contractual social order? For what distributive purposes does the law attempt regulation? The controversial conclusions of this study suggest that the law plays an insignificant role in the construction of markets, and that law and lawyers could provide better assistance by using indeterminate regulation that permits the recontextualization of legal reasoning. Legal regulation of contracts concerned with redistributive tasks, such as redressing unfairness, countering unjust power relations, and improving access to justice, is evaluated both with respect to the objectives of regulation and the search for the most efficient and efficacious form of regulation. The argument in the book is that control of unfairness is both desirable and practicable, that power relations should be modified for the sake of efficiency, and that better access to justice is unhelpful to the resolution of contractual disputes.